The Principal’s Behaviour in Building Teachers’ Trust at State Islamic Senior High Schools - Murtopo, Ali; Risnita, Risnita; Rosadi, Kemas lmron (Yayasan Sembilan Pemuda Indonesia, 2025)
The purpose of this research is to analyse the behaviour of the heads of madrasahs in building trust among teachers in Riau Province, identify the main reasons behind the inability of heads of madrasahs to build trust among teachers, and to find effective leadership behaviours to enhance that trust. This study employs a qualitative method with a descriptive approach to deeply explore the leadership dynamics of the heads of madrasahs in building trust among teachers. Data were collected through in-depth interviews, participatory observations, and document analysis at three research locations. Data analysis was conducted using a flowing data analysis technique to identify key patterns in leadership practices and their impact on teacher trust. Data validity was ensured through data triangulation from various sources and methods, as well as by confirming findings with research participants. The conclusions of the study indicate that increasing teacher involvement in decision-making processes, more effective communication, and support for professional development are key elements in building trust among teachers. At MAN 1 Pekanbaru, increasing teacher participation in decision-making and improving communication effectiveness are priorities. At MAN 1 Indragiri Hulu, a shift from an authoritative to a more inclusive leadership style is needed. Meanwhile, at MAN 1 Indragiri Hilir, there is a need for further improvements in communication and professional development support. The recommendation of this study is to adopt a participatory and communicative leadership approach to create a harmonious and trusting educational environment.